Determinants of Intention of Using Mortgage in Financing Home Ownership in Surabaya - Anastasia, Njo; Thiosalim, Lidya Priskila; Malelak, Mariana Ing (APMBA (Asia Pacific Management and Business Application), 2021)
Expensive prices of houses compels an individual to make a purchase through a third party. This study aims to test the determinants of intention to use mortgage in financing home ownership in Surabaya. The sample was selected using purposive sampling form the population of Surabaya citizens who intended to use home ownership mortgage (Kredit Pemilikan Rumah, KPR). The data was analyzed is SmartPLS. This study finds that subjective norms, perceived behavioral control, knowledge of mortgage, and religiosity significantly affects the intention to use mortgage. Furthermore, attitude, however, does not affect it. The result of this study benefits bankers so that they are able to actively inform consumers about their mortgage products, to raise consumer’s intention to use them. Consumers will also be able to choose mortgage products that suit them best, and they can have a sense of security and convenience during the loan term.